Keputusan Pembelian Ditinjau dari Kualitas Pelayanan, Variasi Produk dan Promosi di Indomaret: Studi pada Indomaret di Kecamatan Laweyan Surakarta - Viony Yusrania Mayantika; Sri Hartono; Supawi Pawenang (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The aim of this research is to determine the influence of Service Quality, Product Variations and Promotion partially or simultaneously on Purchasing Decisions at Indomaret, Laweyan District, Surakarta. This type of research uses quantitative descriptive methods. The population was taken from all Indomaret consumers in the Laweyan area of Surakarta, an infinite number and a sample of 100 respondents. This research uses a purposive sampling technique. Questionnaires were used for data collection. The data analysis method uses statistical analysis, namely multiple linear regression test, F test, t test and coefficient of determination (R2). The results state that Service Quality, Product Variations and Promotion have a positive and significant partial or simultaneous effect on Purchasing Decisions at Indomaret, Laweyan District, Surakarta.